2018
DOI: 10.1155/2018/8568694
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Hypochlorous Acid Solution on Nasal Discharge from Patients with Chronic Rhinosinusitis

Abstract: Purpose The antibacterial effect of hypochlorous acid (HOCl) solution on nasal secretion of patients with chronic rhinosinusitis (CRS) was investigated. Materials and Methods Five swab specimens were collected from the middle meatus of CRS patients. The first one was placed directly in a Thanswab tube while all of the others were placed randomly into 4 glass tubes containing either HOCl solution, normal saline (NS), 75% alcohol, or povidone-iodine (PVPI) solution for one minute in the first part and for 5 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…On the other hand, Wu et al, 11 found that there is no good antibacterial effect after soaking specimens into antiseptic solutions in general. However, this could be explained by the different methodology they applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Wu et al, 11 found that there is no good antibacterial effect after soaking specimens into antiseptic solutions in general. However, this could be explained by the different methodology they applied.…”
Section: Discussionmentioning
confidence: 99%
“…8, 9 Recently, HOCl solution displayed bactericidal effects when employed as a nasal irrigant to treat pediatric chronic sinusitis. 10,11 Some disadvantages of using HOCl have been facing researchers as it was found to be highly corrosive and gradually losing its bactericidal effect with longterm preservation, therefore conditions of long-term storage and safety measures must be applied. Where the safety standard concentration within the World Health Organization for invivo use or drinking water is 5 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Hypochlorous acid (HClO), which is known as a potent broad-spectrum antibacterial agent, has shown strong antimicrobial (antibacterial, fungicidal or virucidal) effect in nasal formulations [146,147].…”
Section: Nasal Delivery Of Hypochlorous Acidmentioning
confidence: 99%
“…Hypochlorous acid (HClO) is a potent broad-spectrum fast-acting antibacterial agent with a favourable safety profile [14]. In nasal formulations, it has shown bactericidal, fungicidal, or virucidal effects [15,16].…”
Section: Introductionmentioning
confidence: 99%